2017
DOI: 10.1002/jcop.21912
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in perceived social support and social service use: Associations with maternal depression and head start participation

Abstract: Using the Head Start Impact Study data, this study examined racial disparities in maternal perceptions of social support and social service receipt, and their associations with depression. Associations between Head Start participation and these variables were also studied. A total of 3,269 mothers were included (n = 971 Black, 1,086 Hispanic, and 1,212 White). Compared to White mothers, Hispanic mothers indicated perceiving less assistance from social supports. Black and Hispanic mothers were less likely to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Recent studies have indicated that Black mothers experience mental health disparities specific to differences in the risks for experiencing mental illness (Boyd et al., 2011; Ceballos, Wallace, & Goodwin, 2017; Glasheen et al., 2015; Ko, Rockhill, Tong, Morrow, & Farr, 2017; Lee, & Rispoli, 2017) and the number of adverse experiences compared to White mothers (CDC, 2008; Ertel et al., 2011; Kurz, 2006; Mukherjee et al., 2018). More specifically, risk factors associated with mental health concerns, such as increased depressive symptoms, anxiety symptoms, and distress, include race (African American), age (young), socioeconomic status (SES; lower SES), income (below the poverty level), employed status (unemployed), level of stress (higher stress), number of children (more than one), and racism (Ceballos et al., 2017; Glasheen et al., 2015; Ko et al., 2017; Manuel et al., 2012; Mitchell & Ronzio, 2001; Reid & Taylor, 2015; Siefert, Williams, Finlayson, Delva, & Ismail, 2007; Wisner et al., 2013, Vesga‐Lopez et al., 2008).…”
Section: Social and Cultural Context Of Maternal Mental Health And Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that Black mothers experience mental health disparities specific to differences in the risks for experiencing mental illness (Boyd et al., 2011; Ceballos, Wallace, & Goodwin, 2017; Glasheen et al., 2015; Ko, Rockhill, Tong, Morrow, & Farr, 2017; Lee, & Rispoli, 2017) and the number of adverse experiences compared to White mothers (CDC, 2008; Ertel et al., 2011; Kurz, 2006; Mukherjee et al., 2018). More specifically, risk factors associated with mental health concerns, such as increased depressive symptoms, anxiety symptoms, and distress, include race (African American), age (young), socioeconomic status (SES; lower SES), income (below the poverty level), employed status (unemployed), level of stress (higher stress), number of children (more than one), and racism (Ceballos et al., 2017; Glasheen et al., 2015; Ko et al., 2017; Manuel et al., 2012; Mitchell & Ronzio, 2001; Reid & Taylor, 2015; Siefert, Williams, Finlayson, Delva, & Ismail, 2007; Wisner et al., 2013, Vesga‐Lopez et al., 2008).…”
Section: Social and Cultural Context Of Maternal Mental Health And Supportsmentioning
confidence: 99%
“…In practice, infant mental health professionals encourage individuals who self‐report mental health problems or met the criteria associated with increased risk for mental illness to be screened, diagnosed, and treated, if clinically indicated (Kurz, 2006). However, the literature suggests that Black mothers are less likely to access and use formal mental health services (Ertel et al., 2011; Glasheen et al., 2015; Lee, & Rispoli, 2017; Smith et al., 2009). Perceived “underutilization” from a Eurocentric standpoint approaches the problem from an individual deficit lens, blaming women for failing to make use of available resources.…”
Section: Social and Cultural Context Of Maternal Mental Health And Supportsmentioning
confidence: 99%
“…The wording of screening questions and the amount of paperwork involved, along with mistrust, perceived stigma, and negative prior experiences seeking resources disproportionately pose barriers to engagement with clinic‐based screening and referral for people of color and historically marginalized groups (Spain et al, 2021; Pfeiffer et al, 2022; Ronis et al, 2022). Service access poses its own set of inequities (Gadson et al, 2017; Lee & Rispoli, 2017; Sandhu et al, 2022). Identifying practices and strategies to support healthcare and early childhood partners to screen and coordinate service provision in different clinic and community contexts can inform the future efforts to spread and scale clinic‐based approaches to mitigating health disparities and addressing negative SDH.…”
Section: Introductionmentioning
confidence: 99%
“…A more focused understanding of the pandemic's impact on parental health and well-being in households with young children in racially and ethnically minoritized communities is needed [8], given the pre-existing systemic inequities in family income, housing, healthcare, employment, and education that these communities have faced due to structural racism in the U.S. [9] and the increased vulnerability that occurs during the early childhood period for families [10,11]. For example, racial and ethnic minority mothers are at greater risk of postpartum depression and report lower levels of social support and greater declines in income during the first postpartum year, compared to white mothers [10][11][12].…”
Section: Introductionmentioning
confidence: 99%